Preparasi dan Karakterisasi Sifat Fisikokimia Multikomponen Ketoprofen dengan Koformer Proline: Preparation and Characterization Physicochemical Properties of Ketoprofen with Proline Coformers - Helen Sonita; Salman Umar; Erizal Zaini (JURNAL FARMASI DAN MAKANAN, 2023)
Ketoprofen is a non-steroidal anti-inflammatory compound (NSAID) which has low solubility in water. The aim of this study was to increase the dissolution rate of ketoprofen by forming multicomponent ketoprofen-Proline with ratio of 1:1, 1:2, and 2:1 by using solid state grinding method. Samples were characterized by Powder X-Ray Diffractometry (PXRD), Differential Scanning Calorimetry (DSC), Fourier Transform Infrared (FTIR) Spectroscopy, scanning electron microscope (SEM) analysis, solubility test, dissolution rate profile, and stability test. The results indicates the formation of a eutectic mixture of ketoprofen-Proline. From the study of the ketoprofen–proline eutectic mixture, the eutectic point in ratio 2:1 was obtained 54,763℃. The PXRD spectra did not form new crystal habit, the highest solubility test of the eutectic mixture of ketoprofen-proline showed an increase respectively 2,671 times in ratio 1:2. Stability test showed that ketoprofen-proline was not stable at 75% relative humidity (RH) 40℃ degree during 6 months storage because it deformed the solid phase into the liquid phase.